2015
DOI: 10.1016/j.amsu.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of acute appendicitis and inflammatory myofibroblastic tumor of the small intestine: A case report

Abstract: IntroductionInflammatory myofibroblastic tumor as a rare neoplastic lesion is seen most commonly in the pulmonary system. Beside the presence of limited number of inflammatory myofibroblastic tumors of the gastrointestinal tract in the literature, co-existence with acute appendicitis has not been reported before.Presentation of caseA 27-year-old woman admitted to emergency department with acute abdominal pain at the right lower quadrant. The initial diagnosis was as acute appendicitis. Intraoperatively, a mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(22 reference statements)
0
5
0
4
Order By: Relevance
“…Limited cases regarding the coexistence of intestinal malrotation with intussusception and inflammatory myofibroblastic tumor with acute appendicitis have been reported in previous studies [8,9]. This unique report adds precious clinical and imaging findings of acute appendicitis coexisting with multiple spontaneously resolving intussusceptions, to the literature.…”
Section: Discussionmentioning
confidence: 74%
“…Limited cases regarding the coexistence of intestinal malrotation with intussusception and inflammatory myofibroblastic tumor with acute appendicitis have been reported in previous studies [8,9]. This unique report adds precious clinical and imaging findings of acute appendicitis coexisting with multiple spontaneously resolving intussusceptions, to the literature.…”
Section: Discussionmentioning
confidence: 74%
“…IMFTs were first well described in the lungs and later became recognized in extrapulmonary locations [2] , [3] , [4] , [5] − 43% of extra-pulmonary involvement affects the mesentery and omentum [7] . Gastrointestinal (GI) involvement is rare however there are reports of involvement of any part of GI tract [2] , [6] , [7] , [8] , [9] . It occurs mostly in childhood and young adults but patients of any age and sex can be affected [2] .…”
Section: Discussionmentioning
confidence: 99%
“…5 The World Health Organization classifies IMT as tumors of intermediate biological potential since both local recurrence and metastases are possible. 1,2 Coffin et al 3 showed that IMT developed at a mean age of 9.7 years, and in 36 of 84 cases (43%), IMTs arose from the mesentery and omentum. Höhne et al 6 reviewed 443 publications from between 2009 to February 2014; their reports involved 938 patients and 956 organ sites.…”
Section: Case Historymentioning
confidence: 99%
“…The World Health Organization classifies IMTs as tumors of intermediate biological potential since both local recurrence and metastases are possible. 1,2 IMT affects children and young adults predominantly, but patients of any age and sex can be affected. 3 Gastrointestinal tract (GIT) IMT presents with clinical symptoms of anemia, loss of appetite or weight, fecal blood positive, abdominal pain, GIT obstruction, or intussusception.…”
mentioning
confidence: 99%